NUMERICAL SOLUTION OF ABSORBING BOUNDARY CONDITION IN PADÉ APPROXIMATION - Mohammad Mahfuzh Shiddiq (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2015)
natural domain require an artificial boundary condition for reducing the size of its natural domain. One of these boundary conditions is absorbing boundary condition. This paper will construct an absorbing boundary condition with Padé approximations and numerical solution by finding the difference equation.